2021
DOI: 10.7759/cureus.19920
|View full text |Cite
|
Sign up to set email alerts
|

The Coronaid Program: An App-Based Telemedicine Tool for Triaging, Testing, Treating and Monitoring COVID-19 Patients in Mexico

Abstract: Objective: To describe the results of a Mexican telemedicine program for patients with coronavirus disease 2019 (COVID-19).Methods: An observational retrospective study was conducted to analyze and describe the baseline demographic and clinical characteristics of patients who received medical video consultations for respiratory symptoms.Results: A total of 1,148 video consultations were given from March to September 2020 via Sofía's mobile app. A total of 580 patients sought medical consultation regarding resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…People are reducing activities outside the home to prevent the transmission of COVID-19, including visiting health care facilities. Remote information exchange using telemedicine applications is considered effective in providing care to COVID-19 patients, especially those living in remote areas, as reported in several studies (16)(15) 17 . In addition, studies have also reported increased people's access to medical care during the COVID-19 pandemic using telemedicine 15 .…”
Section: Methodsmentioning
confidence: 99%
“…People are reducing activities outside the home to prevent the transmission of COVID-19, including visiting health care facilities. Remote information exchange using telemedicine applications is considered effective in providing care to COVID-19 patients, especially those living in remote areas, as reported in several studies (16)(15) 17 . In addition, studies have also reported increased people's access to medical care during the COVID-19 pandemic using telemedicine 15 .…”
Section: Methodsmentioning
confidence: 99%